Self-Control and Unhealthy Body Weight: The Role of Impulsivity and Restraint - Deborah A. Cobb-Clark; Sarah C. Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2022)
We examine the relationship between trait self-control and body weight. Data from a population representative household survey reveal that limited self-control is strongly associated with both objective and subjective measures of unhealthy body weight. Those with limited self-control are characterized by reduced exercising, repeated dieting, unhealthier eating habits, and poorer nutrition. We propose an empirical method to isolate two facets of self-control limitations—high impulsivity and low restraint. Each has differential predictive power. Physical activity, dieting, and overall body weight are more strongly associated with restraint; impulsivity is more predictive of when, where, and what people eat.
Keywords: D91; I12; 330; brief self-control scale; obesity; body mass index; diet; exercise